ISOLATION OF 7A-EPIALEXAFLORINE FROM LEAVES OF ALEXA-GRANDIFLORA - A UNIQUE PYRROLIZIDINE AMINO-ACID WITH A CARBOXYLIC-ACID SUBSTITUENT AT C-3 - Pereira, A; Kaplan, M; Maia, J; Gottlieb, O; Nash, R; Fleet, G; Pearce, L; Watkin, D; Scofield, A (1991)
The isolation and identification by X-ray crystal structure analysis of 7a-epialexaflorine (1R,2R,3S,7S,7aR)-3-carboxy-1,2,7-trihydroxypyrrolizidine, the first example of a naturally occurring pyrrolizidine-3-carboxylic acid, from Alexa grandiflora is described. © 1991.